2016
DOI: 10.1261/rna.056218.116
|View full text |Cite
|
Sign up to set email alerts
|

mRNA bound to the 30S subunit is a HigB toxin substrate

Abstract: Activation of bacterial toxins during stress results in cleavage of mRNAs in the context of the ribosome. These toxins are thought to function as global translational inhibitors yet recent studies suggest each may have distinct mRNA specificities that result in selective translation for bacterial survival. Here we demonstrate that mRNA in the context of a bacterial 30S subunit is sufficient for ribosome-dependent toxin HigB endonucleolytic activity, suggesting that HigB interferes with the initiation step of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 50 publications
(82 reference statements)
2
19
0
Order By: Relevance
“…Surprisingly, we also found the density representing uS2 to be completely absent from our cryo-EM maps. In the 30S subunit, uS2 binds in the solvent face (convex face) of the subunit stably anchoring its two domains to the 16S rRNA and typically is fully visible in previously obtained X-ray (Schureck et al, 2016;Wimberly et al, 2000) and cryo-EM In cryo-EM, to preserve the specimen in their hydrated state, one spread the sample in a thin layer of buffer solution supported in the cryo-EM grid right before plunging the grid into liquid ethane to freeze the liquid layer into vitreous ice. In the vitrification device used in our experiments, the time that elapses between the blotting of the grid to form the thin layer and the vitrification is typically 1 second.…”
Section: Exposure Of the 30s Subunits To The Air-water Interface In Tmentioning
confidence: 88%
“…Surprisingly, we also found the density representing uS2 to be completely absent from our cryo-EM maps. In the 30S subunit, uS2 binds in the solvent face (convex face) of the subunit stably anchoring its two domains to the 16S rRNA and typically is fully visible in previously obtained X-ray (Schureck et al, 2016;Wimberly et al, 2000) and cryo-EM In cryo-EM, to preserve the specimen in their hydrated state, one spread the sample in a thin layer of buffer solution supported in the cryo-EM grid right before plunging the grid into liquid ethane to freeze the liquid layer into vitreous ice. In the vitrification device used in our experiments, the time that elapses between the blotting of the grid to form the thin layer and the vitrification is typically 1 second.…”
Section: Exposure Of the 30s Subunits To The Air-water Interface In Tmentioning
confidence: 88%
“…The YafO toxin was shown to be a ribosome-dependent endoribonuclease that cleaves mRNAs 11-13 bases downstream of the initiation codon (Zhang et al, 2009;Christensen-Dalsgaard et al, 2010). Such cleavage event was speculated to be located near the mRNA entrance tunnel rather than at the A site as determined for the RelE-like toxins (Schureck et al, 2016a). Although initially YafO was considered a RelE-like toxin (Christensen-Dalsgaard et al, 2010), the lack of structural information about this toxin or its interaction with ribosome lead to YafO being classified as a separate family (Leplae et al, 2011).…”
Section: Mrna Cleavage In the Ribosome By Rele Toxinsmentioning
confidence: 99%
“…RelE Nsp , Sinorhizobium meliloti RelE Sme and Treponema denticola RelE Tde (Prysak et al, 2009;Goeders et al, 2013). P. vulgaris HigB cleaves A-rich codons (Hurley and Woychik, 2009;Schureck et al, 2016b), and was shown to cleave the 30S bound mRNA, indicating that it can interfere with the initiation step of translation after IF1 dissociation (Schureck et al, 2016a). The AAA and other A-rich codons are the most frequent at the beginning of the ORFs in E. coli (Sato et al, 2001).…”
Section: Mrna Cleavage In the Ribosome By Rele Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…A HigB homolog encoded in the Proteus vulgaris Rts1 plasmid associates with the 50S ribosomal subunit in polysome profiling assay and it cleaves mRNA at AAA sequences and other cleavage sites regardless of the frame [16]. In contrast, according to the crystal structure, HigB also binds to the 30S ribosomal subunit [20].…”
mentioning
confidence: 99%